INDUCTION OF SHOOT FORMATION IN STRAWBERRY (Fragaria × Ananassa DUCH.) CLONE BAT 1 IN VITRO USING VARIOUS TYPES AND CONCENTRATIONS OF CYTOKININS - Pauline Elisabeth; Anne Nuraini; Murgayanti; Muhammadiyah (Berita Biologi, 2026)
Strawberry (Fragaria × ananassa Duch.) is a high-value subtropical horticultural crop. One promising local variety under development is clone BAT 1. To accelerate propagation, tissue culture techniques are needed, especially during bud initiation, which is influenced by cytokinin type and concentration. This study used a Completely Randomized Design (CRD) with 7 treatments and 4 replications, using Murashige and Skoog (MS) medium supplemented with Thidiazuron (TDZ) and 2-Isopentyl adenine (2-iP) at concentrations of 0; 0.50; 0.75; 1 ppm TDZ and 1; 2; 3 ppm 2-iP. The procedures included explant preparation, sterilization of equipment and area, stock solution preparation, media formulation and sterilization, explant sterilization, and planting into treatment media. Results showed that cytokinins at 0.50–1 ppm significantly enhanced bud number, leaf number, culture height, and fresh weight.  The most effective treatments were 1 ppm 2-iP (5.24 buds; 5.90 leaves; 2.23 cm height) and 0.50 ppm TDZ (1.36 g fresh weight), indicating their potential for improving in-vitro propagation of clone BAT 1.